PELATIHAN LANGKAH-LANGKAH MEMULAI EKSPOR UNTUK UMKM DI KABUPATEN PEKALONGAN - Stacia Reviany Mege; Anafil Windriya; Maya Aresteria (LPPM UNIMA, 2020)
Indonesia’s trade deficit is one problem that government plan to overcome by several strategies including increasing exports. The contribution of Micro, Small and Medium Enterprise (MSME) also known as UMKM to total export in 2019 was approximately 14%. Despite their large contribution to overall GDP, UMKM are expected to participate more active in international trade by exporting their products. However, their perspective on internal or external barriers inhibit them to start exporting. The purpose of this community service is to empower UMKM in Pekalongan regency with knowledge about export and to help preparing them to enter international trade. Four steps were undertaken throughout the process, started by surveying and followed by deciding UMKM partner. The third and the fourth steps were preparation and training activity respectively. Upon participating in the training, the participants have shown positive attitude toward export and have gained understanding about export preparation. This community service will be held continuously.